2008
DOI: 10.1093/bja/aen133
|View full text |Cite
|
Sign up to set email alerts
|

Pleth variability index to monitor the respiratory variations in the pulse oximeter plethysmographic waveform amplitude and predict fluid responsiveness in the operating theatre

Abstract: PVI, an automatic and continuous monitor of DeltaPOP, can predict fluid responsiveness non-invasively in mechanically ventilated patients during general anaesthesia. This index has potential clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
219
2
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(244 citation statements)
references
References 37 publications
(19 reference statements)
9
219
2
5
Order By: Relevance
“…Studies have shown the usefulness of this noninvasive dynamic parameter in mechanically ventilated patients in the operating room and in the intensive care unit (ICU). 6,10,19 Conversely, other studies have concluded that PVI was of limited value in predicting fluid responsiveness in laparoscopic surgery 20 and in the ICU setting, respectively. 21 Several observations have shown the limitations of this parameter.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies have shown the usefulness of this noninvasive dynamic parameter in mechanically ventilated patients in the operating room and in the intensive care unit (ICU). 6,10,19 Conversely, other studies have concluded that PVI was of limited value in predicting fluid responsiveness in laparoscopic surgery 20 and in the ICU setting, respectively. 21 Several observations have shown the limitations of this parameter.…”
Section: Discussionmentioning
confidence: 97%
“…9 The PI can be expressed by the following formula: PI = (AC/DC) x 100 [%]. 10 The value PVI is a noninvasive dynamic variable that reflects fluid status. It is calculated from the changes in PI over one or more complete respiratory cycles in mechanically ventilated patients using the following formula 10 :…”
Section: Measurementsmentioning
confidence: 99%
“…PVI -это точный неинвазивный показатель ге-модинамического ответа на водную нагрузку у па-циентов, находящихся на искусственной вентиля-ции легких [19]. Имеются также данные о том, что вариабельность амплитуды пульсовой волны отра-жает преднагрузку у пациентов на спонтанном ды-хании [13,22,36].…”
Section: мониторинг г емодинамики особенности у новорож денныхunclassified
“…[54][55][56][57][58] Solus-Biguenet et al, for instance, found a weak correlation of 0.29. 54 Nevertheless, despite this weak correlation, the majority of fluid responsiveness studies suggest that the respiratory variation in the PPG tracing is predictive of the hemodynamic response to fluid loading, [59][60][61][62][63] although this finding is not universal. 64,65 Surprisingly, despite the fact that the physiologic meaning of arterial respiratory variation has been understood for decades, extrapolation to the PPG waveform was completely missed by the manufacturers of pulse oximeters who considered this information ''noise'' and filtered it out through the application of high-pass filters.…”
Section: Fluid Responsivenessmentioning
confidence: 99%